Meanings of materials : proefschrift ter verkrijging van de graad van doctor aan de Technische Universiteit Delft - Karana, Elvin, ....- (2009)
The variety of applications for materials in product design has remarkably increased over the last decade. A particular material may be embodied in a kitchen appliance as well as in an office accessory. Even though the technical qualities of the material remain the same in both applications, the expressive meanings attributed to the material may differ considerably. This makes it hard to sustain that a specific material has a definite meaning; that is, neither plastics are cheap surrogate materials, nor is ceramics old-fashioned nowadays. Product designers consider various factors in order to express their intentions through materials. How a material is used, who the user is, and how the material is produced can all be important in their decision for creating particular meanings. The main goal of this study is to explore how people attribute meanings to materials for the aim of supporting designers to involve meanings of materials in materials selection process.
Keywords: Materialen